PENANGANAN DAN PENEGAKAN HUKUM DALAM PEMILU: PERAN BAWASLU DAN IMPLIKASI PERDATA - Yolivia, Yolivia Gracia Lubis; Sinaga, Budiman N.P.D. (Jurnal Media Informatika, 2025)
The purpose of the research in this journal is to analyze the administrative aspects in handling and enforcing the Law in elections, with a focus on the role of Bawaslu as the implementer of the Enforcement of the Administrative Law. This study uses the Normative Juridical method, with a literature study approach, analyzing laws related to elections, election data, and previous studies. The results of the research in this journal also show that Bawaslu has a very important role in supervising and cracking down on violations during the implementation of the elections, including violations that have implications for civil lawsuits. However, there are several obstacles in the enforcement of Civil Law in the Election, such as lack of public awareness, limited Bawaslu resources, and a long legal process. This journal also recommends several steps to increase the effectiveness of handling and enforcing civil law in elections, such as increasing legal socialization, strengthening the capacity of Bawaslu, and awareness of the legal process.